2002
DOI: 10.1103/physrevlett.88.177403
|View full text |Cite
|
Sign up to set email alerts
|

Momentum-Resolved Charge Excitations in a Prototype One-Dimensional Mott Insulator

Abstract: We report momentum-resolved charge excitations in a one-dimensional (1D) Mott insulator studied using high resolution inelastic x-ray scattering over the entire Brillouin zone for the first time. Excitations at the insulating gap edge are found to be highly dispersive (momentum dependent) compared to excitations observed in two-dimensional Mott insulators. The observed dispersion in 1D cuprates ( SrCuO2 and Sr2CuO3) is consistent with charge excitations involving holons which is unique to spin-1/2 quantum chai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
57
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 32 publications
3
57
0
Order By: Relevance
“…24 Most of the numerical work has focused on the regime of large U , which is appropriate to describe strong Mott insulators such as Sr 2 CuO 3 . 5 We note that the DSF has strikingly different line shapes in the weak and strong coupling limits. For noninteracting electrons, U = 0, the DSF can be calculated exactly and corresponds to the density of states of an electron-hole pair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Most of the numerical work has focused on the regime of large U , which is appropriate to describe strong Mott insulators such as Sr 2 CuO 3 . 5 We note that the DSF has strikingly different line shapes in the weak and strong coupling limits. For noninteracting electrons, U = 0, the DSF can be calculated exactly and corresponds to the density of states of an electron-hole pair.…”
Section: Introductionmentioning
confidence: 99%
“…One motivation for this is that questions about features of the excitation spectrum of 1D systems, such as the persistence of spin-charge separation at high energies, have become relevant with the improvement in the resolution of momentum-resolved experiments. [4][5][6][7][8] In addition, ultracold atoms trapped in optical lattices have emerged as a new means to study coherent dynamics of 1D models, including integrable ones which are not realizable in condensed matter systems. 9 At the same time, significant progress has been achieved in developing analytical [10][11][12][13][14][15][16][17][18][19][20][21][22] and numerical [23][24][25] techniques to study dynamical correlation functions in the high energy regime where conventional Luttinger liquid theory 26,27 does not apply.…”
Section: Introductionmentioning
confidence: 99%
“…More recently this technique has been applied to various cuprates including high-T c materials 2,3,4,5,6,7,8,9,10,11 and other highly-correlated electron systems. 12,13,14 A recent RIXS study near the Cu K edge in undoped La 2 CuO 4 (LCO) has revealed three features in its charge excitation spectrum. 5 Two features, labeled A and B, appear at energy transfers ω = 2.2 eV and 3.9 eV, respectively; these features show the largest intensity enhancement at an incident photon energy of E i = 8.991 keV.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to ARPES, RIXS is really bulk sensitive and applicable to insulators with high resistivity, where the electron correlation is even stronger. 1,2,5,9 However, high energy resolution RIXS is rather demanding because of their poor count rate. For this purpose, high photon flux in a small spot size and a highly efficient analyzer crystal are required.…”
mentioning
confidence: 99%
“…1,2 This technique is intriguing to clarify bulk electronic states of strongly correlated insulators, which are under a keen general interest in decades. 3,4,5 For metallic systems, highresolution angle-resolved photoemission (ARPES) is promising to detect their occupied states.…”
mentioning
confidence: 99%